Inovasi Pmt (Pemberian Makanan Tambahan) Sebagai Bentuk Gerakan Cegah Stunting Di Desa Ciderum Kecamatan Caringin Kabupaten Bogor - Sevtian Akmalul Khoer; Agnia Rahmawati; Aisyah Indriani Rachmat; Mareta Arum Purwita Sari; Putri Adri Sindoro Hakim; Wilda Apriani; Tria Wulandari; Muhammad Ari Suryana; Muhammad Fakih Kurniawan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Pregnant women and toddlers need to get special attention in terms of nutritional intake which can cause malnutrition so that they are at risk of stunting. One way to deal with nutritional problems is the provision of Supplementary Food (PMT) made from local food in the form of protein from animals to support cell growth and strengthen the immune system. The aim of making this innovative product is as a movement to prevent stunting which is made from chicken meat and quail eggs. This freezing process includes preparatory stages in the form of forming an outreach concept and discussions about innovative products. Meanwhile, to make this happen in the form of delivery of the innovation product. Next, a questionnaire was given as a means of evaluation. The results of the research on the level of preference for this innovative product in terms of taste and consumption power show a good category, which means it has the potential to be accepted and can be used as a food innovation for children.